Neolitização e Megalitismo: o recinto megalítico das Fontainhas (Mora, Alentejo Central - Calado, Manuel (2010)
The excavation of the megalithic enclosure of Fontainhas (Mora), on 2005,has confirmed, with new data, the chronological attribution of the monument to the Early Neolithic, mostly decorated pottery and microlithic artefacts. Some new elements about ritual, like the reuse of quern stones inside the sockets of the menhirs, or the astronomical orientations (solar and lunar) of the stones outside the enclosure, have also been obtained. The survey around the site reinforced, by its side, the information given by the artefacts recovered in the dig of the monument: a network of settlements, spanning from the Early Neolithic to the Early Bronze Age, has been registered. The main surprise, in this domain,was a Mesolithic occupation, expectable, until a certain point, according to some recent data from contiguous areas, and to the geographical context, in the limits of the Terciary basin of the Tejo.